Occurrence of Anastrepha fraterculus (Diptera: Tephritidae) on raspberry (Rubus idaeus) and blackberry (Rubus fructicosus) fruit cultivated in a semiarid-temperate highland valley of Tucumán, Argentina - Meneguzzi, Natalia G. (2016)
The Mediterranean fruit fly (CC), Ceratitis capitata, and the South American fruit fly (AF), Anastrepha fraterculus, are serious polyphagous insects considered pests of several plant families. Both species are widely distributed in Argentina, including the province of Tucumán, where their occurrence was reported in high-elevation valleys, affecting several cultivated and wild fruit species. Provided that raspberry (Rubus idaeus) and blackberry (Rubus fructicosus) are minor (but in expansion) crops in Tucumán, and the spectrum of pests affecting these crops is not very well known, the aim of this study was to determine the occurrence of AF and CF on these crops. During 2016, ripe fruit from plants of the blackberry cultivar ?878? and the raspberry cultivar ?Heritage? were collected from an organic orchard in Tafí del Valle (26°52′S, 65°41′W, 2014 m altitude). Sampling dates were Feb-5, 19 and 24, and Mar-10 and 23. Fruit sample was divided into 2 replicates of 20-30 fruits each, and placed into clamshells (20×20×30 cm) with sand at the bottom for larvae pupation. Clamshell lids were removed and replaced by voile fabric to allow air exchange and to prevent insects from escaping. They were kept at about 25°C and 60-70% RH for 20 days. Tephritid adults and pupae from each clamshell were recovered weekly, identified and counted. The reported fruit infestation level was based on the number of adults per fruit number and fruit weight obtained from each sample. Means and standard deviations (SD) were calculated. This is the first report of the occurrence of the South American fruit fly on blackberry and raspberry in Tucumán (Argentina).